The prediction of foreign language achievement on social competence in Chinese adolescent EFL learners - Jiahuan Zhang; Man Wang; Wen Ma (Humanities & Social Sciences Communications)
Abstract Being a successful bilingual comes with numerous advantages in human development, and much work has been centered on the cognitive benefits of bilingualism. While research in first language development suggests language ability, as a foundation for communication, affects the development of social competence, less is known about whether and how bilingualism relates to individuals’ social competence. The present study investigates the relationship between foreign language achievement and social competence of Chinese EFL learners in a junior high sample. The ability of emotion regulation is also considered as a regulating factor. Regression analysis is employed to examine the predictive effects of foreign language achievement and emotion regulation on social competence, controlling for gender, age, and non-verbal intelligence. The cross-sectional findings indicate that foreign language achievement correlates positively with and can predict social competence. In addition, the relationship between foreign language achievement and social competence is modulated by emotion regulation. Our findings highlight the significance of foreign language learning for social competence development, at least in Chinese adolescent EFL learners.